Single-amino acid variants reveal evolutionary processes that shape the biogeography of a global SAR11 subclade - Tom O Delmont; Evan Kiefl; Ozsel Kilinc; Ozcan C Esen; Ismail Uysal; Michael S Rappé; Steven Giovannoni; A Murat Eren (eLife, 2019)
Members of the SAR11 order Pelagibacterales dominate the surface oceans. Their extensive diversity challenges emerging operational boundaries defined for microbial 'species' and complicates efforts of population genetics to study their evolution. Here, we employed single-amino acid variants (SAAVs) to investigate ecological and evolutionary forces that maintain the genomic heterogeneity within ubiquitous SAR11 populations we accessed through metagenomic read recruitment using a single isolate genome. Integrating amino acid and protein biochemistry with metagenomics revealed that systematic purifying selection against deleterious variants governs non-synonymous variation among very closely related populations of SAR11. SAAVs partitioned metagenomes into two main groups matching large-scale oceanic current temperatures, and six finer proteotypes that connect distant oceanic regions. These findings suggest that environmentally-mediated selection plays a critical role in the journey of cosmopolitan surface ocean microbial populations, and the idea ‘everything is everywhere but the environment selects’ has credence even at the finest resolutions.